Analisis Karakteristik Fisik Subdas Air Lematang dan Subdas Air Selangis Besar Terhadap Debit Banjir Puncak - Alharia Dinata (JURNAL ILMIAH BERING'S, 2017)
Watershed has distinctive physical characteristics between the and another watershed like a river basin shape, the length of the main river, watershed area, the order of the river, the river network density, and the slope of the river. From these physical characteristics, it can be used to analyze peak discharge in a watershed which has not yet had a river hydrometry station. Synthetic unit hydrograph (HSS) is one of the most widely used empirical approaches in estimating unit hydrograph in a watershed. HSS GAMA I is a method that has been developed in Indonesia with results close to the data in the field, this method uses physical data characteristic watershed in calculating Qp. The purpose of this research is to analyze the influence of physical characteristics of sub-watershed Air Lematang and Sub-watershed Air Selangis Besar to Qp and to analyze the flood discharge of the two sub-watershed designs. The analysis result shows that Qp sub-watershed Air Lematang is 9.8 m³ / d with subdistrict area 295.88 km² and TR 2.08 hours with main river length 49,93 km. Qp Sub-watershed Air Selangis Besar 11.13 m³ / d with an area of 288.02 km² and TR 1.61 hours with the main river length of 34.51 km. Q100Tr sub-watershed Air Lematang and sub-watershed of Air Selangis Besar were 873.44 m³ / d and 826,86 m³ / d respectively. The effect of physical characteristics of the two sub-basins on Qp is broadly understood and the shape of sub-watershed and TR is influenced by the source factor and the length of the main river.